Dehydration of mango (Mangifera indica L. cv Katchamita) slices. - Debuyan, Alile Grace Donaire (2016.)
Katchamita mango grown in the Philippines but underutilized can be utilized in the production of dried mango. In this study, Katchamita mangoes were dried using two drying temperature and time combinations, 60°C for 10 hours (treatment A) and 80°C for 5 hours (treatment B). Sensory evaluation revealed that there was no significant difference between the two treatments. Results from the General Descriptive Analysis showed that dried mangoes from treatment B were tougher in texture than those from treatment A. The dried mango slices were then observed for changes in water activity, titrable acidity, total plate count (TPC) and yeast and mold count (YMC) within a 14-day storage period. Results showed that drying at 80°C for 5 hrs resulted to significantly lower activity (0.597 to 0.615) and increased titrable acidity (0.50% to 0.57%) of the dried mango slices. Microbiological assessment showed negligible population in terms of TPC and YMC for both treatments and were also found to be within acceptable limits during the storage period according to the New Zealand Ministry of Health (1995). Results suggest that drying of Katchamita mangoes can result to a dried product that conforms to standards. Drying at a higher temperature had a significant effect on texture, water activity, titrable acidity, TPC and YMC. A study on the optimization of Katchamita mango dried at 80°C for 5 hrs and utilization of Katchamita mangoes into other food products such as jams, wine, jellies puree, pickles, and powder are recommended.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Mango; Katchamita indica L. ev Katchamita; Drying